Sedentary Lifestyle And Eating Habits As Risk Factors For Obesity In Adolescents. - belounis, rachid; bouadjnak, Kamel (sports creativity, 2025)
In recent decades, obesity has become increasingly rare in many countries and is no longer merely a cosmetic issue associated with overeating. Defined as a metabolic disorder characterized by excessive accumulation of adipose tissue, obesity is now considered a genuine disease, so much so that the World Health Organization (WHO) has declared it "the first non-communicable epidemic in history" (Depres, 2007, p. 5). The prevalence of obesity is increasing among both children and adults. Its long-term consequences are of grave concern, particularly for children. According to the WHO, nearly 10% of children and adolescents aged 5 to 17 years worldwide are obese. Numerous studies have demonstrated significant clinical and metabolic abnormalities associated with childhood obesity, both in the short and long term. In fact, obesity that develops during childhood and adolescence leads to an estimated 50 to 80% increase in adult mortality due to its association with hypertension, diabetes, and cardiovascular complications (Hala, Y., 2008, p. 19). The rapid increase in obesity rates among children and adolescents, which will lead to health problems and social difficulties, justifies intensive research efforts to better understand the determinants of overweight and to identify appropriate preventive strategies. In Algeria, profound socio-economic structural changes are paving the way for a dietary and demographic shift characterized by lifestyle changes: altered eating habits (increased calorie consumption and disruption of eating patterns and balance) and sedentary behaviors linked to decreased physical activity and sports and increased sedentary activities (television, video games). This sudden shift creates a lifestyle-altering environment where individuals predisposed to overweight can become obese. Our work is of paramount importance given the role of epidemiological studies as a tool for decision-making and strategy development in public health. Its main objectives are: - to estimate the prevalence of obesity among school-aged adolescents, - to identify the dietary factors associated with obesity in terms of nutritional balance. In Algeria, we lack national data on overweight and obesity among adolescents. Local studies conducted in specific regions of Algeria do not allow us to determine the prevalence at the national level. Nevertheless, these reports contribute to raising awareness of the scale of this epidemic. The only data we have is that published by the Department of Epidemiology and Preventive Medicine of Bouzaréah (SEMEP) in 2011, which estimated the prevalence of overweight and obesity among children aged 12 to 17 at 18%. A 2005 study by the Olamara organization indicated a prevalence of obesity and overweight of 9.92% among children aged 10 to 12. In Setif in 2006/2007, school screenings revealed an overweight rate of 13.5%. Other reports from health services indicate that in the western region of the country, in El Bayadh and Tiniat El Had, the prevalence of overweight (including obesity) was estimated at 12% in 2005. In Sidi Bel Abbès in 2007, a study found that the prevalence of overweight and obesity was 8.3% among young people aged 13 to 18. Regarding abdominal obesity in children and adolescents, to the best of our knowledge, there are few studies in Algeria that address this problem. The only study we were able to obtain is the study by Ben Mohamed et al. (2010), which was conducted on adolescents aged between 12 and 19 years, and which highlights the relationship between abdominal obesity in children and high blood pressure.